REKONSTRUKSI POLITIK HUKUM PIDANA TERHADAP EKSAMINASI TUNTUTAN BEBAS DALAM KASUS VALENCYA - Naratama, Tantri; Sitompul, Rina Melati (Universitas Dharmawangsa, 2024)
Law enforcement is basically a process of implementing ideas, because law enforcement is an effort to implement ideas about justice, legal certainty, and social good. Law enforcement is an effort to make the law a guideline for perpetrators of traffic violence or legal relations in the life of society and the state. In Valencya's case, the public was concerned that the public prosecutor charged the defendant Valencya with violating the letter of Article 45 paragraph (1) and Article 5 of the Domestic Violence Law Number 23 of 2004 and demanded a prison sentence of 1 year. Because the charge constituted emotional abuse of the man, the public reacted unfairly, so the deputy commissioner paid special attention to the case, which then led to an investigation into the case.The purpose of this research is to find out what is the legal basis for the release of the defendant at the request of the prosecutor in Valencia and how this research is applied in prosecutorial cases in terms of the decisions taken in the Valencya case study. This research approach uses normative legal methods, where this research is conducted on the basis of primary legal materials, by examining existing theories and concepts, legal principles and legal provisions that are closely related to this research. The results of this research appear to lead to legal discovery and reform.